Participation - Bishop, Claire (London : Whitechapel ; Cambridge, Mass. : MIT Press, 2006)
- Theoretical frameworks. The poetics of the Open work / Umberto Eco ##- The death of the author / Roland Barthes ##- The negation of the autonomy of art by the Avant-garde / Peter Bürger ##- The inoperative community / Jean-Luc Nancy ##- Poetics of relation / Édouard Glissant ##- Chaosmosis: an ethico-aesthetic paradigm / Félix Guattari ##- Problems and transformations in critical art / Jacques Rancière. Artists writings. Towards a situationist international / Guy Debord ##- Notes on the elimination of the audience / Allan Kaprow ##- Dance in my experience / Hélio Oiticica ##- Letters 1968-69 / Lygia Clark and Hélio Oiticica ##- Project for the experimental art series, Rosario / Graciela Carnevale ##- Report of a day's proceedings at the Bureau for Direct Democracy / Joseph Beuys and Dirk Schwarze ##- I am searching for field character / Joseph Beuys ##- Ten appearances ##- Notes on funk, I-II / Adrian Piper ##- On democracy ##- Transnacionala/A journey from the East to the West / Eda Cufer ##- The Baudouin/Boudewijn experiment: a deliberate, non-fatalistic, large-scale group experiment in deviation / Carsten Höller ##- The battle of Orgreave / Jeremy Deller ##- No ghosts in the wall / Rirkrit Tiravanija ##- 24h Foucault / Thomas Hirschhorn. Critical and curatorial positions. Relational aesthetics / Nicolas Bourriaud ##- Social aesthetics / Lars Bang Larsen ##- What is a station? / Molly Nesbit, Hans Ulrich Obrist, Rirkrit Tiravanija ##- Chat rooms / Hal Foster.
Includes bibliographical references (p. 200-203) and index.
boek